Mortality options: the point of view of an insurer - Maren Diane Schmeck; Hanspeter Schmidli (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
We consider the surplus process of a life insurer who is able to buy a securitisation product to hedge mortality in a discrete time framework. Two cohorts are considered: one underlying the securitisation product and one for the portfolio of the insurer. In our main result we show that there exists a unique strategy that maximises the expected utility of the insurer. Our findings are illustrated by a tractable model for mortality catastrophe risk.
urn:nbn:de:0070-pub-29357981
Keywords: 330; mortality option; optimal strategy; maximal utility; exponential utility